2017
DOI: 10.3390/rs9090929
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Drought-Induced Tree Mortality in Sierra Nevada Forests with Time Series of Satellite Data

Abstract: Abstract:A five-year drought in California led to a significant increase in tree mortality in the Sierra Nevada forests from 2012 to 2016. Landscape level monitoring of forest health and tree dieback is critical for vegetation and disaster management strategies. We examined the capability of multispectral imagery from the Moderate Resolution Imaging Spectroradiometer (MODIS) in detecting and explaining the impacts of the recent severe drought in Sierra Nevada forests. Remote sensing metrics were developed to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 71 publications
2
46
0
Order By: Relevance
“…have not yet been documented beyond short-term (<5 years) associations during severe drought (Byer & Jin, 2017;Potter, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…have not yet been documented beyond short-term (<5 years) associations during severe drought (Byer & Jin, 2017;Potter, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Detection of dead trees may be important for forest practitioner especially with respect to bark beetle attacks, when abandoned trees (dead-dry trees) may indicate close presence of the beetle near to these trees. Dead trees detection through satellite imagery was described for example described in [51] or more recently in [52]. Hart and Veblen [51] utilized a National Agriculture Imagery Program (NAIP) for training the Landsat Climate Data Records (LDCR) dataset and reported that on tree level the red-green index was higher for grey attacked trees and on stand level index the decrease (lower values) of NDVI could be noticed.…”
Section: Assessing Forest Health and Physiology Statusmentioning
confidence: 99%
“…Overall accuracy reported was over 88%. Byer and Jin [52] also deployed Random Forest algorithm for classification and regression producing accuracy of 96.3% for the classification Random Forest and a RMSE of 7.19 dead trees per acre for the regression Random Forest. Relatively innovative approach was presented by Baker et al [53], where the authors mapped dead trees attacked by pine beetle by assessing MODIS time series with continuous snow cover, when gaps were used to detect continuous ground snow coverage and a snow-free overstory, and so to detect pixels with crown mortality.…”
Section: Assessing Forest Health and Physiology Statusmentioning
confidence: 99%
“…Secondly, its consequences can be experienced at relatively broad geographic scales and simultaneously across landscapes [26]. Thirdly, drought stimulates other forest disturbances such as fire [27] and insect outbreaks [28], which further impair tree productivity, sometimes leading to tree mortality [29,30]. Lastly, it is challenging to determine the onset and cessation of drought episodes since vegetation responds in different ways [31], making it difficult to evaluate drought using costly and spatially restricted field-based measurements [32].…”
Section: Introductionmentioning
confidence: 99%